Scaffold nanoestruturado utilizando-se celulose bacteriana/fosfatos de cálcio para regeneração óssea - Daltro, Paula Braga [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The production of a bacterial cellulose scaffold / calcium phosphates (CB / PCa) obtained from standard simulated body fluid (SBF) and modified SBFs were stabilished by Aparecida (2009) were incorporated to optimize calcium phosphate phase formation in order to enhance bone regeneration. Samples from bacterial cellulose have been coated with calcium phosphate per SBF established by Ali et al. 2009 and six other SBF conditions changed. Two differente bacterial cellulose were compared, the membrane product of dried hydrogel and commonly used in reaserch was after dried incorporated with the SBFs and the hydrogel in natura incorporated with the PCa was then dried and processed into hydrogel powder, both produced under the same coating conditions. The phase formation of HA and other calcium phosphates were visualized in all samples. In this work, the influence of the standard SBF and modified SBFs (1, 2, 3, 4, 5 and 6) were analyzed chosen in the formation of calcium phosphate phases on the surface of the bacterial cellulose membrane. It was also studied the influence of this biofilm / CaP on cell pre-osteoblast cells viability. The characterization of the samples was done by scanning electron microscopy (SEM) X-ray diffraction - XRD, spectroscopy in the infrared Fourier transform (FTIR) and thermal analysis (TGA, DSC, DTG). The biological testing character was done on both conditions by the MTT reduction method. Cytotoxicity was not identified in any of the samples tested.

A produção de um scaffold de celulose bacteriana/fosfatos de cálcio (CB/PCa) obtidos a partir de SBF e SBFs modificadas foi produzida para otimizar o processo de regeneração óssea. As amostras de celulose bacteriana foram recobertas com fosfatos de cálcio por SBF estabelecido por Thomazini (2009) e seis outras condições de SBF modificadas. Foram comparadas a membrana de celulose bacteriana e o hidrogel transformado em pó, ambos produzidos nas mesmas condições de recobrimento. A formação da fase HA e outros fosfatos de cálcio, foram visualizadas em todas as amostras. Neste trabalho, foram analisadas as influências dos SBF padrão e dos SBFs modificadas (SBF 1, 2, 3, 4, 5 e 6) escolhidos na formação das fases de fosfatos de cálcio na superfície da membrana de celulose bacteriana. Também foi estudado a influência deste biofilme/CaP na viabilidade celular e na adesão e proliferação de células pré-osteoblásticas. A caracterização das amostras foi feita através de microscopia eletrônica de varredura (MEV) difração de raios X - DRX, espectroscopia na região do infravermelho por transformada de Fourier (FTIR) e análises térmicas (TGA, DSC, DTG). O teste biológico de foi feito em ambas as condições testadas e condicionadas. Não foi identificada citotoxicidade em nenhuma das amostras.
Keywords: Celulose; Fosfato de calcio; Regeneração óssea; Biofilme; Materiais biomédicos; Cellulose